Management of uncomplicated gastric ulcer in community pharmacy: a pseudo‑patient study (2019)
Background Increasing role of community pharmacists sometimes demands the diagnoses of minor ailments using appropriate questioning skills and recommendation of over-the-counter medications to patients seeking self-care. Objective To evaluate community pharmacists’ questioning and diagnostic skills of minor ailment complaints, and the appropriateness of medication(s) recommendations made. Setting One hundred and thirty-one community pharmacies in Ibadan, Nigeria. Method A cross-sectional survey employing pseudo-patient study method. The pseudo-patient visited 131 community pharmacies from June 2017 to January 2018 and complained of stomach ache. The conversation between the pharmacists and pseudopatient were audio-taped and transcribed verbatim. Two criteria were used to evaluate the questioning skill of the community pharmacists. One of the criteria was developed by a six-membered panel and had 13 questions while the other contained five questions:—Who is it for? What are the symptoms? How long have the symptoms been present? Action taken? and Medication used.? Questioning skill of the community pharmacists was classified based on the median scores of these two criteria as: poor, moderate and optimal. The diagnoses made by the community pharmacists from the pseudo-patients complaints were compared with the expected diagnosis of uncomplicated gastric ulcer caused by the use of ibuprofen. Recommendations for the pseudo-patients minor ailment were also compared with the Nigeria standard treatment guideline. Main outcome measure Pharmacists’ questioning skill, types of diagnosis made and appropriateness of medications recommended. Results The median scores for the questioning skill criterion containing 5 and 13 questions were 2 and 4, respectively; showing poor questioning skill. Differential diagnoses of gastric ulcer, dyspepsia, gastroesophageal reflux, and hyperacidity were made by 92 (67.4%) pharmacists but 3 (2.3%) correctly diagnosed the pseudo-patients’ minor ailment as uncomplicated gastric ulcer caused by short-term use of ibuprofen. Antacids were recommended in line with the standard treatment guideline by 46 (35.7%) pharmacists while proton pump inhibitors were recommended by 6 (4.7%) pharmacists. None advised the withdrawal of the provocative factor according to the treatment guideline. Conclusion The questioning skill of the community pharmacists in this setting was poor. Few community pharmacists diagnosed the pseudo-patients’ minor ailment correctly. Also, recommendations were mostly inappropriate compared with the standard treatment guideline.